Beban Ganda Perempuan dalam Cengkeraman Budaya Patriarki - Frastika Utami, Manda Ayu; Mukdin, Khairani (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2025)
This study aims to comprehensively analyze the social and cultural factors that contribute to the dual burden experienced by women. It also seeks to examine the extent to which patriarchal norms and structural systems influence the division of labor in both domestic and public spheres, where women are often expected to manage household responsibilities alongside formal employment. Employing a qualitative literature review approach, this article explores recent academic literature that discusses gender relations, unpaid domestic work, and the persistence of patriarchal social structures in the Indonesian context. The findings indicate that patriarchal norms remain deeply entrenched in society, compelling women to shoulder double responsibilities despite their increasing and active participation in the public and professional sectors. This ongoing imbalance has adverse effects on women’s physical and mental health and significantly diminishes their overall quality of life. The study is expected to make a meaningful contribution to the development of a more holistic and inclusive theoretical framework for understanding gender inequality. It also aims to serve as a foundation for the formulation of gender-responsive public policies that can better address the specific needs and challenges faced by working women.